A wave model of refraction of laser beams with a discrete change in intensity in their cross section and their application for diagnostics of extended nonstationary phase objects. (31st August 2015) - Raskovskaya, I L
Abstract A beam model with a discrete change in the cross-sectional intensity is proposed to describe refraction of laser beams formed on the basis of diffractive optical elements. In calculating the wave field of the beams of this class under conditions of strong refraction, in contrast to the traditional asymptotics of geometric optics which assumes a transition to the infinite limits of integration and obtaining an analytical solution, it is proposed to calculate the integral in the vicinity of stationary points. This approach allows the development of a fast algorithm for correct calculation of the wave field of the laser beams that are employed in probing and diagnostics of extended optically inhomogeneous media. Examples of the algorithm application for diagnostics of extended nonstationary objects in liquid are presented.